Parent Satisfaction in the Pediatric ICU - Latour, Jos; van Goudoever, J.; Hazelzet, J. (2008)
Parents are important partners who collaborate with the multidisciplinary team to improve quality of care. This article discusses a framework for action toward quality improvement in pediatric intensive care by parental empowerment through parent satisfaction with care. Incorporating the concepts of family-centered care and parental needs and experiences into a parent satisfaction instrument may provide quality improvement projects based on the empowerment of parents and eventually may facilitate the implementation and evaluation of quality initiatives. © 2008 Elsevier Inc. All rights reserved.